Using Direct Skills Teaching to Improve Job Skills for Persons With Disabilities. Issue 2 (7th June 2019) - Oursler, Janice; Lu, Weili; Herrick, Samantha; Harris, Kevin
Abstract : This study evaluated whether a direct skills training (DST) approach for persons with disabilities can better prepare participants for job interviews. Twenty graduate students in a master's program in rehabilitation counseling at various agency internship sites were trained in a 4‐session Presenting Qualifications curriculum based on DST administered to 126 participants in 20 group settings. Participants reported greater confidence and preparedness in the interview process, in answering difficult questions, and in highlighting past accomplishments after the group. Results support the feasibility of training entry‐level rehabilitation counselors in the DST approach to teach job interview skills to individuals with disabilities.